2016
DOI: 10.1021/acs.jctc.5b01045
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Platinum-Aryl Interaction with Amyloid-β Peptide

Abstract: Ligand field molecular mechanics (LFMM), density functional theory (DFT) and semi-empirical PM7 methods are used to study the binding of two Pt(II)-L systems to an N-terminal fragment of the amyloid-β peptide, where L = 2,2-bipyridyl or 1,10-phenanthroline. Molecular dynamics simulations are used to explore the conformational freedom of the peptide using LFMM combined with AMBER molecular mechanics parameters. We establish a modelling protocol, allowing for identification and analysis of favorable platinum-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 55 publications
0
10
0
1
Order By: Relevance
“…During the LMMD search, the platinum centre was set at a fixed potential to avoid premature termination of the conformational search. 31 Semi-empirical calculations were performed using the Molecular Orbital PACkage (MOPAC) in its 2012 39 version, with the Parametric Model 7 (PM7) method 40 and the Conductor-like Screening Model (COSMO) model of aqueous solvation 41 . Overlay plots and images were obtained using Chimera imaging software 42 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the LMMD search, the platinum centre was set at a fixed potential to avoid premature termination of the conformational search. 31 Semi-empirical calculations were performed using the Molecular Orbital PACkage (MOPAC) in its 2012 39 version, with the Parametric Model 7 (PM7) method 40 and the Conductor-like Screening Model (COSMO) model of aqueous solvation 41 . Overlay plots and images were obtained using Chimera imaging software 42 .…”
Section: Methodsmentioning
confidence: 99%
“…This gives δFεε 'the flexibility and generality of quantum mechanics with the speed of molecular mechanics.' 23 which has allowed success in the modelling of a range of Jahn-Teller active Cu II systems 27 , spin states of Ni and Fe complexes 28 as well as some Pt II -biomolecule studies 29,30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ][ 21 ] In addition, Streltsov et al used a combination of EXAFS and DFT to probe local binding environment at Pt and derive structural models for the interaction of platinum complexes with Aβ16 and Aβ42. [ 22 ] Recently, we showed that ligand field molecular mechanics (LFMM) [ 23 ][ 24 ][ 25 ] is an appropriate method to probe the binding of Pt to fragments of Aβ, characterising the effect of Pt complexes on limiting conformational freedom of the peptide [ 26 ] and the role of ligand variation in complexes formed and 3D conformation adopted. [ 27 ] In this work, we extend this approach to examine the dynamical behaviour of a typical Pt-Aβ adduct using molecular dynamics simulations and LFMM description of metal coordination coupled with conventional molecular mechanics (MM) for the peptide.…”
Section: Introductionmentioning
confidence: 99%
“…Streltsov et al 29 used a combination of EXAFS and density functional theory (DFT) to conrm binding through His residues, while our group has used DFT, semi-empirical and molecular mechanics methods to examine Pt binding to model peptides. [30][31][32] The intrinsically disordered nature of Ab means that such studies struggle to sample the full conformational exibility of the peptide. To address this possible shortcoming, and to provide further details of possible Pt(phen)-peptide interactions and the effect of metal coordination on peptide structure at a molecular level, we performed replica-exchange molecular dynamics (REMD) simulations of the platinum complex interacting with both the Nterminal Ab16 fragment and complete Ab42 peptides.…”
Section: Introductionmentioning
confidence: 99%